Femtosecond Transient Absorption of Zinc Porphyrins with Oligo(phenylethylnyl) Linkers in Solution and on TiO(2) Films - Chang, Chih-Wei; Luo, Liyang; Chou, Chung-Kung; Lo, Chen-Fu; Lin, Ching-Yao; Hung, Chen-Shiung; Lee, Yuan-Pern; Diau, Eric Wei-Guang (My University, 2009)
We measured femtosecond transient absorption of dye solutions and TiO(2) films sensitized with two zinc porphyrins (PE1 and PE4) to investigate the interfacial dynamics of electron transfer in relation to the dependence of cell performance on the length of the linker (Lin, C.-Y.; Lo, C.-F.; Luo, L.; Lu, H.-P.; Hung, C.-S.; Diau, E. W.-G. J. Phys. Chem. C 2009, 113, 755-764). For both porphyrins adsorbed on TiO(2) films with S(1) excitation (lambda(ex) = 620 nm), the transient absorption kinetics probed at 630 nm and 4.9 mu m are complementary to each other because only the excited-state and ground-state species were observed at 630 nm whereas only the charge-separation intermediates were observed at 4.9 mu m. The transient of the PE1/TiO(2) film shows a single exponential decay with a large offset, whereas the transient of the PE4/TiO(2) film displays a biexponential decay with a small offset. Because of the existence of an additional ps component, the amount of free delocalized electrons (offset signal) in PE4/TiO(2) is smaller than that in PEI/TiO(2). Our results imply that back electron transfer at the TiO(2)/dye interface is an important factor to be considered to account for the cell performance of a device.